Unexpected PF6 Anion Metathesis during the Bischler–Napieralski Reaction: Synthesis of 3,4-Dihydroisoquinoline Hexafluorophosphates and Their Tetrahydroisoquinoline Related Alkaloids - Puerto Galvis, Carlos E.; Macías, Mario A.; Kouznetsov, Vladimir V. (Synthesis, 2019)
A series of N-phenethylcinnamamides were subjected to the Bischler–Napieralski reaction to furnish diverse 1-styryl-3,4-dihydroisoquinolines. We noticed that the desired products were unstable when the reaction was performed under conventional solvent conditions. However, when [bmim]PF6 was used as the reaction media, the nature of the Bischler–Napieralski reaction promoted an unusual in situ ionic interchange between this ionic liquid and the dihydroisoquinoline core that led to the stabilization of the desired 1-styryl-3,4-dihydroisoquinolines, allowing their isolation as hexafluorophosphate salts. Finally, the one-pot reduction/reductive methylation process afforded the N-methyl derivatives, establishing that our findings can be an efficient and useful strategy for the concise synthesis of tetrahydroisoquinoline alkaloids.
Keywords: cinnamamide; Bischler–Napieralski reaction; dihydroisoquinoline hexafluorophosphate; Dysoxylum alkaloid; tetrahydroisoquinoline